Juridical Analysis of Judges' Decisions in Settling Grant Disputes from a Maslahah Perspective - Fauzi, Mohammad Yasir; Muslim, Muslim; Winarsih, Tri (ASAS, 2024)
Grants are tabarru' actions but often cause envy among the parties concerned or indirectly concerned. With several facts and cases regarding the withdrawal of grant assets for various reasons.  As the case of grant disputes in the Kudus Religious Court with case number 314/Pdt.G/2020/PA.Kds. Jo. Number 372/Pdt.G/2020/PTA.Smg. Jo. 658 K/Ag/2021. The purpose of this article is to know and analyse the judge's decision in resolving grant disputes from a maslahah perspective, seen from the type of research using library research or literature study, the primary data source is the decision of the Kudus Religious Court with case number 314/Pdt.G/2020/PA.Kds. Jo. Number 372/Pdt.G/2020/PTA.Smg. Jo. 658 K/Ag/2021, while secondary legal sources are maslahah perspectives both from book sources, journal articles and so on, then data analysis using qualitative analysis techniques.  The results of the study explain that the decisions of the courts of first instance and appeal are cancelled because this case is a case that should be the authority of the religious courts. As the decision of the panel of judges of the Kudus Religious Court Number 314/Pdt.G/2020/Pa.Kds, and the Semarang Religious High Court in its decision Number 372/Pdt.G/2020/PTA.Smg did not apply justice and expediency and even legal certainty. Article 49 of the Religious Courts Law is the basis for legal certainty in this case so that the party who filed the lawsuit did not get justice that the object of the case was the only property that had been owned and also in the two decisions did not achieve happiness for many parties, this is in line with the Supreme Court's decision Number 658 K/Ag/2021. Therefore, the decision of the Indonesian Supreme Court in examining and deciding the case is in accordance with the applicable legal theory and in accordance with the principle of kemashlahatan or maslahah theory in Islamic law.Keywords: Grant; Maslahah; Tabarru' Act